El quinto en discordia - Davies, Robertson, 1913-1995; Puig, Valentí; Cervera, Natalia; Davies, Robertson, 1913-1995. (Barcelona, España : Libros del Asteroide S.L.U., 2012)
Ramsay is a man twice born, a man who has returned from the hell of the battle-grave at Passchendaele in World War I decorated with the Victoria Cross and destined to be caught in a no man's land where memory, history, and myth collide. As Ramsay tells his story, it begins to seem that from boyhood, he has exerted a perhaps mystical, perhaps pernicious, influence on those around him.
First book of Trilogía de Deptford.
Sequel: Mantícora.
Online resource; title from ePub title page (Digitalia, viewed March 20, 2018)
Keywords: World War, 1914-1918 -- Veterans -- Fiction; Christian hagiography -- Fiction; School principals -- Fiction; History teachers -- Fiction; Bachelors -- Fiction; Canada -- Fiction; Guilt -- Fiction; Psychological fiction; Didactic fiction; Electronic books